Developing a model to explore the information seeking behaviour of farmers - Mahindarathne, M.G.P.P; Min, Qingfei (Journal of documentation, 2018)
Purpose Generating an in-depth understanding of information needs and seeking behaviour is important both for restructuring existing agricultural information systems (ISs) and for creating new ISs. Many information seeking models have been developed over the years, most are narrowly focused on a specific role or discipline. However, no such specific model has been developed in reference to agriculture or an allied discipline. Thus, the purpose of this paper is to develop a model to explore the information seeking behaviour (ISB) of farmers. Design/methodology/approach The model proposed in this paper is based on Wilson’s model. The theoretical insights and empirical evidences comprehended at the study were embedded into Wilson’s model to develop a model that explores the ISB of farmers. The proposed model was quantitatively evaluated using empirical data gathered through a survey of 289 farmers. Furthermore, the model was qualitatively evaluated by subject experts against criteria of simplicity, comprehensiveness, exactness, generality and clarity. Findings The key finding of this study is the model developed to explore the ISB of farmers. The adapted model provides theoretical and empirical bases for exploring farmers’ ISBs. Thus, the model will be useful in developing valuable design insights to apply to user-centred agricultural ISs. Originality/value The originality of this study relates to its demonstration of how existing models can be reconsidered and adapted based on related literature and then tested and presented as adapted models. The proposed model will be useful to promote informational studies in agriculture.